Bimetal catalyst for furfural hydrogenation and preparation method thereof
Bimetallic catalysts were prepared by combining block copolymer template agent synthesized using the ATRP method in the furfural hydrogenation reaction, which solved the problems of high catalyst cost, low efficiency and environmental pollution in the prior art, and achieved an efficient and environmentally friendly furfural hydrogenation reaction.
Patent Information
- Application Number
- CN202411671709.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, the catalyst used for hydrogenation of furfural is high in cost, has low catalytic efficiency, has harsh reaction conditions, and contains highly toxic elements to seriously pollute the environment.
The amphiphilic block copolymer template agent was synthesized by atom transfer radical polymerization (ATRP) method, and the combination of specific metal precursors and carrier precursors was carried out to conduct multivariate induced self-assembly to form a highly ordered mesoscopic structure, and a bimetallic catalyst was prepared.
It has achieved a low cost, high catalytic efficiency, mild reaction conditions, and no severe pollution to the environment. It has high catalytic activity, good selectivity, and a yield of up to 99%.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bimetallic catalysts, in particular to a bimetallic catalyst for furfural hydrogenation and a preparation method thereof. Background Art
[0002] Furfural (FAL) with the molecular formula of C5H4O2 is an important and commonly used chemical intermediate. It is the main raw material for the production of resins, lubricants, adhesives and plastics. It is obtained through hydrogenation, oxidation, hydrogenation-hydrogenolysis and other reactions to obtain chemicals with higher added value, such as furfuryl alcohol, tetrahydrofurfuryl alcohol, furan, 1,5-pentanediol and succinic acid, which are widely used in synthetic resins, rubber, fragrances, pharmaceutical processes and other fields.
[0003] Bimetallic catalysts are composite catalysts composed of two different metals, prepared by specific methods such as sol-gel method, impregnation method or alloying technology. One metal acts as the active center and the other metal acts as an auxiliary agent, which work together in the catalytic reaction to improve the activity and selectivity of the catalyst. The bimetallic catalyst prepared using polymer as a template has simple process and convenient operation. The prepared catalyst has good dispersion, high activity and high catalytic efficiency, is easy to mass produce, and has great development potential.
[0004] At present, the catalyst commonly used in foreign countries for hydrogenation of aldehyde to produce sugar alcohol is Cu-Cr catalyst, which has high catalytic activity and relatively mild reaction conditions. However, Cr-containing catalysts are highly toxic and cause irreversible pollution to the environment. Therefore, in the domestic existing technology, Cu catalysts are used as a substitute to reduce pollution to the environment. However, compared with foreign products, domestic products have higher costs, lower yields of catalytic aldehyde reactions, harsh reaction conditions, and poor competitiveness, so further research and development and improvement are needed.
[0005] In summary, in order to solve the above problems, it is of great significance to prepare a bimetallic catalyst for furfural hydrogenation which has low cost, high catalytic efficiency, mild reaction conditions and no severe toxicity to the environment. Summary of the invention
[0006] The object of the present invention is to provide a bimetallic catalyst for furfural hydrogenation and a preparation method thereof, so as to solve the problems raised in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a bimetallic catalyst for furfural hydrogenation comprises the following steps: S1: Synthesis of template: Polyethylene oxide monomethyl ether and 2-bromoisobutyryl bromide are reacted to obtain an initiator, which is then reacted with styrene to form a bromine-terminated block copolymer and grafted with poly(ethylene glycol) acid to obtain a template; S2: Add the template into tetrahydrofuran, stir evenly, add the metal precursor, stir at 50-60°C for 1-2h, add the carrier precursor, stir at 55-65°C for 4-5h, transfer to an oven and heat treat at 50-100°C for 15-18h to obtain a mesoporous material preform; S3: transferring the mesoporous material preform to a muffle furnace, and calcining it at 550-900° C. in a reducing gas atmosphere to obtain a bimetallic catalyst.
[0008] Preferably, the synthesis of the template comprises the following steps: (1) After polyethylene oxide monomethyl ether is completely dissolved in anhydrous pyridine, the mixture is vigorously stirred, and 2-bromoisobutyryl bromide is gradually added dropwise in an ice-water bath, with the addition time controlled at 20-30 min. The mixture is then stirred at 20-30 °C for 10-12 h, purified, filtered, washed, and dried to obtain initiator A; (2) Initiator A, pentamethyldiethylenetriamine, cuprous bromide and styrene are added to a reaction bottle, mixed, degassed, stirred at 110-120° C. for 1-3 h, purified, precipitated and dried to obtain a bromine-terminated block copolymer; (3) adding anhydrous ether to the bromine-terminated block copolymer and stirring evenly, adding allyl magnesium bromide in an ice-water bath, stirring for 1 to 2 hours, purifying, and drying to obtain an allyl-terminated copolymer; (4) Add the allyl-terminated copolymer into tetrahydrofuran and stir evenly, add mercapto-polyethylene glycol-carboxylic acid and benzoin dimethyl ether, stir under ultraviolet light for 20 to 22 hours, purify, precipitate, and dry to obtain a template.
[0009] Preferably, the molecular weight of the polyethylene oxide monomethyl ether is 5000~8000; the metal precursor comprises a copper salt and a nickel salt in a molar ratio of 1.5~1.6:1; the copper salt comprises one of copper chloride, copper nitrate, and copper acetylacetonate; the nickel salt comprises one of nickel chloride, nickel nitrate, and nickel acetylacetonate; the carrier precursor comprises one of acetylacetone, citric acid, and polyvinyl pyrrolidone.
[0010] Preferably, the mercapto-polyethylene glycol-carboxylic acid includes one of mercapto-diethylene glycol-carboxylic acid, mercapto-triethylene glycol-carboxylic acid and mercapto-tetraethylene glycol-carboxylic acid.
[0011] Preferably, the mesoporous material preform comprises the following raw materials, in parts by mass: 10-12 parts of template, 30-35 parts of tetrahydrofuran, 5-6 parts of metal precursor, and 8-9 parts of carrier precursor.
[0012] Preferably, the template comprises an allyl-terminated copolymer, mercapto-diethylene glycol-carboxylic acid, and benzoin dimethyl ether in a molar ratio of 1:1.5-1.7:0.9-1.1.
[0013] Preferably, the initiator A comprises the following raw materials, in parts by mass: 4.8 to 5.2 parts of polyethylene oxide monomethyl ether, 0.24 to 0.26 parts of 2-bromoisobutyryl bromide; the bromine-terminated block copolymer comprises the following raw materials, in parts by mass: 4.8 to 5.0 parts of initiator A, 0.17 to 0.18 parts of pentamethyldiethylenetriamine, 0.14 to 0.15 parts of cuprous bromide, 5.1 to 5.3 parts of styrene; the allyl-terminated copolymer comprises the following raw materials, in parts by mass: 9.5 to 10.5 parts of bromine-terminated block copolymer, 0.14 to 0.15 parts of allylmagnesium bromide.
[0014] Wherein, during the heat treatment process, the temperature is 50-100°C, preferably 60-80°C, and the time is 15-18 hours; during the calcination process, the temperature is 550-900°C, preferably 650-800°C, and the time is 6-8 hours.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts atom transfer radical polymerization (ATRP) to synthesize an amphiphilic block copolymer template. By adjusting experimental parameters such as the molecular weight of the polymer raw material, reaction temperature, polymerization time, monomer and ligand dosage during the polymerization process, the molecular weight of the template is regulated, and then the volume and effective stacking parameters of the hydrophilic end and the hydrophobic end of the block copolymer are regulated to obtain a template that meets the use requirements. The template is used as a structure-directing agent to select a suitable mesoporous skeleton precursor, i.e., a metal precursor and a carrier precursor, so that the metal precursor and the carrier precursor form a complex, thereby increasing the molecular force between the metal source and the template, slowing down the precursor hydrolysis / cross-linking rate, and realizing the multi-inducing self-assembly of the template, the carrier precursor, and the metal precursor, thereby realizing the atomic-level bimetallic alloy functional unit in the block copolymer-carbon precursor composite, and constructing a highly ordered mesoscopic structure. The material is then placed in an oven for heat treatment to further cross-link and solidify the skeleton structure, and is calcined at high temperature in a reducing atmosphere. This can remove the template while preventing pore collapse, promote the migration and diffusion of metal atoms to form a cluster structure, and ultimately construct a mesoporous-loaded atomic-level bimetallic alloy cluster catalytic material, that is, a mesoporous material with a highly ordered pore arrangement structure.
[0016] (2) The present invention uses polyethylene oxide monomethyl ether with a molecular weight of 5000-8000 as a hydrophilic block, and uses 2-bromoisobutyryl bromide to synthesize an initiator with a bromine atom, so that styrene is polymerized on the basis of a macromolecular segment to form a hydrophobic block, thereby obtaining an amphiphilic block copolymer, and the present invention controls the overall copolymer molecular weight to be 10000-12000. The prepared bimetallic catalyst has the best catalytic activity after the test of the aldehyde hydrogenation experiment. If the molecular weight is too low, the template effect will be weakened, and the stability of the mesoporous material cannot be effectively controlled, resulting in uneven pore size and pore wall, and low specific surface area and porosity of the bimetallic catalyst; if the molecular weight is too high, due to the increased probability of entanglement and penetration between molecular chains, larger and densely structured aggregates will be formed, resulting in a decrease in porosity.
[0017] (3) The present invention utilizes the bromine atoms at the ends of the amphiphilic block copolymer molecules to graft a smaller molecular weight polyglycolic acid, which can further promote the dispersibility of the copolymer molecules in the solvent and improve the uniformity of the pores and pore distances of the mesoporous material. At the same time, its good hydrophilicity can change the hydrophilic / hydrophobic balance of the polymer, improve its self-assembly ability, and enable the catalyst to form a more regular and orderly pore structure. Controlling the grafted chain segments to be smaller molecules can prevent the overall copolymer molecular weight from being too large, reduce the possibility of entanglement and penetration between molecular chains, and reduce the adverse effects on the catalyst pores. Its carboxyl group can further improve the hydrophilicity, and can also coordinate with certain metal ions to enhance the multi-component self-assembly effect and improve the catalyst activity. The present invention also controls the molar ratio of copper salt to nickel salt in the metal precursor to be 1.5~1.6:1, which helps to maximize the catalyst activity, improve selectivity, and reduce the generation of by-products.
[0018] (4) The bimetallic catalyst prepared by the present invention is dispersed at the atomic level, which greatly reduces the proportion of bulk atoms that do not participate in the reaction, can greatly improve the atomic utilization rate of the metal, and reduce the catalyst cost. It is also suitable for transfer hydrogenation technology. The use of isopropanol as a hydrogen source and solvent avoids the use of high-pressure hydrogen. It has advantages in terms of cost and safety. It can achieve a 99% furfuryl alcohol yield at only 160°C. While meeting the catalytic performance requirements, it has the characteristics of less pollution and environmental friendliness. DETAILED DESCRIPTION
[0019] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0020] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and exemplarily include: polyethylene oxide monomethyl ether, cas: 9004-74-4, purity 99%, provided by Liaoning Kelong Fine Chemical Co., Ltd.; 2-bromoisobutyryl bromide, cas: 20769-85-1, purity 99%, provided by Hubei Jusheng Technology Co., Ltd.; pentamethyldiethylenetriamine, cas: 3030-47-5, purity 99%, provided by Mingwei (Shandong) Supply Chain Management Co., Ltd.; allyl magnesium bromide, cas: 1730-25-2, purity 99%, provided by Hubei Xinkang Pharmaceutical Chemical Co., Ltd.; mercapto-diethylene glycol-carboxylic acid, provided by Shanghai Haohong Biomedical Technology Co., Ltd.; acetylacetone, purity 99%, provided by Jinan Century Tongda Chemical Co., Ltd.
[0021] In the following examples, the molecular weight of polyethylene oxide monomethyl ether is 5000, parts by mass, and raw materials are all commercially available.
[0022] Embodiment 1:
[0023] S1: Synthesis of template: (1) Add 5 parts of polyethylene oxide monomethyl ether to 30 parts of anhydrous pyridine and dissolve completely, then stir vigorously, gradually add 0.25 parts of 2-bromoisobutyryl bromide dropwise in an ice-water bath, the addition time is controlled within 25 min, then stir at 25 °C for 11 h, purify, filter, wash and dry to obtain initiator A; (2) 4.9 parts of initiator A, 0.173 parts of pentamethyldiethylenetriamine, 0.143 parts of cuprous bromide, and 5.2 parts of styrene were added to a reaction bottle, mixed, degassed, stirred at 115° C. for 2 h, purified, precipitated, and dried to obtain a bromine-terminated block copolymer; (3) Add 10 parts of bromine-terminated block copolymer to anhydrous ether and stir evenly, add 0.145 parts of allyl magnesium bromide in an ice-water bath, stir for 1.5 hours, purify, and dry to obtain an allyl-terminated copolymer; (4) adding 10.5 parts of allyl-terminated polymer to tetrahydrofuran and stirring evenly, adding 0.31 parts of mercapto-diethylene glycol-carboxylic acid and 0.25 parts of benzoin dimethyl ether, stirring for 20 hours under ultraviolet light, purifying, precipitating, and drying to obtain a template; S2: Add 11 parts of template to 30 parts of tetrahydrofuran, stir evenly, add 5.5 parts of metal precursor (mass ratio of copper chloride to nickel chloride is 1:1.65), stir at 55°C for 1.5h, add 8.5 parts of acetylacetone, stir at 60°C for 4.5h, transfer to an oven and heat treat at 70°C for 16h to obtain a mesoporous material preform; S3: The mesoporous material preform is transferred to a muffle furnace and calcined at 700° C. for 7 h in a reducing gas atmosphere to obtain a bimetallic catalyst.
[0024] Embodiment 2:
[0025] S1: Synthesis of template: (1) After 4.8 parts of polyethylene oxide monomethyl ether was completely dissolved in anhydrous pyridine, the mixture was stirred vigorously, and 0.24 parts of 2-bromoisobutyryl bromide was gradually added dropwise in an ice-water bath. The addition time was controlled within 20 min, and the mixture was stirred at 20 °C for 10 h. The mixture was purified, filtered, washed, and dried to obtain initiator A. (2) 4.8 parts of initiator A, 0.17 parts of pentamethyldiethylenetriamine, 0.14 parts of cuprous bromide and 5.1 parts of styrene were added to a reaction bottle, mixed, degassed, stirred at 110° C. for 1 h, purified, precipitated and dried to obtain a bromine-terminated block copolymer; (3) adding 9.5 parts of bromine-terminated block copolymer to anhydrous ether and stirring evenly, adding 0.14 parts of allyl magnesium bromide in an ice-water bath, stirring for 1 hour, purifying, and drying to obtain an allyl-terminated copolymer; (4) adding 10 parts of allyl-terminated polymer to tetrahydrofuran and stirring evenly, adding 0.3 parts of mercapto-diethylene glycol-carboxylic acid and 0.2 parts of benzoin dimethyl ether, stirring for 20 hours under ultraviolet light, purifying, precipitating, and drying to obtain a template; S2: Add 10 parts of template to 30 parts of tetrahydrofuran, stir evenly, add 5 parts of metal precursor (the mass ratio of copper chloride and nickel chloride is 1:1.6), stir at 50°C for 1 hour, add 8 parts of acetylacetone, stir at 55°C for 4 hours, transfer to an oven and heat treat at 60°C for 15 hours to obtain a mesoporous material preform; S3: The mesoporous material preform is transferred to a muffle furnace and calcined at 650° C. for 6 h in a reducing gas atmosphere to obtain a bimetallic catalyst.
[0026] Embodiment 3:
[0027] S1: Synthesis of template: (1) After 5.2 parts of polyethylene oxide monomethyl ether were completely dissolved in anhydrous pyridine, the mixture was stirred vigorously, and 0.26 parts of 2-bromoisobutyryl bromide was gradually added dropwise in an ice-water bath. The addition time was controlled within 30 min, and the mixture was stirred at 30 °C for 12 h. The mixture was purified, filtered, washed, and dried to obtain initiator A. (2) 5 parts of initiator A, 0.18 parts of pentamethyldiethylenetriamine, 0.15 parts of cuprous bromide, and 5.3 parts of styrene were added to a reaction bottle, mixed, degassed, stirred at 120° C. for 3 h, purified, precipitated, and dried to obtain a bromine-terminated block copolymer; (3) adding 10.5 parts of bromine-terminated block copolymer to anhydrous ether and stirring evenly, adding 0.15 parts of allyl magnesium bromide in an ice-water bath, stirring for 2 hours, purifying, and drying to obtain an allyl-terminated copolymer; (4) adding 11 parts of allyl-terminated polymer to tetrahydrofuran and stirring evenly, adding 0.32 parts of mercapto-diethylene glycol-carboxylic acid and 0.3 parts of benzoin dimethyl ether, stirring for 22 hours under ultraviolet light, purifying, precipitating, and drying to obtain a template; S2: Add 12 parts of template to 35 parts of tetrahydrofuran, stir evenly, add 6 parts of metal precursor (the mass ratio of copper chloride to nickel chloride is 1:1.7), stir at 60°C for 2h, add 9 parts of acetylacetone, stir at 65°C for 5h, transfer to an oven and heat treat at 80°C for 18h to obtain a mesoporous material preform; S3: The mesoporous material preform is transferred to a muffle furnace and calcined at 800° C. for 8 h in a reducing gas atmosphere to obtain a bimetallic catalyst.
[0028] Comparative Example 1: Based on Example 1, the bromine-terminated block copolymer is not grafted with mercapto-diethylene glycol-carboxylic acid, and the other processes remain unchanged, as follows: S1: Synthesis of template: (1) Add 5 parts of polyethylene oxide monomethyl ether to 30 parts of anhydrous pyridine and dissolve completely, then stir vigorously, gradually add 0.25 parts of 2-bromoisobutyryl bromide dropwise in an ice-water bath, the addition time is controlled within 25 min, then stir at 25 °C for 11 h, purify, filter, wash and dry to obtain initiator A; (2) 4.9 parts of initiator A, 0.173 parts of pentamethyldiethylenetriamine, 0.143 parts of cuprous bromide, and 5.2 parts of styrene were added to a reaction bottle, mixed, degassed, stirred at 115° C. for 2 h, purified, precipitated, and dried to obtain a template; S2: Add 11 parts of template to 30 parts of tetrahydrofuran, stir evenly, add 5.5 parts of metal precursor (mass ratio of copper chloride to nickel chloride is 1:1.65), stir at 55°C for 1.5h, add 8.5 parts of acetylacetone, stir at 60°C for 4.5h, transfer to an oven and heat treat at 70°C for 16h to obtain a mesoporous material preform; S3: The mesoporous material preform is transferred to a muffle furnace and calcined at 700° C. for 7 h in a reducing gas atmosphere to obtain a bimetallic catalyst.
[0029] Comparative Example 2: Based on Example 1, the mercapto-diethylene glycol-carboxylic acid was replaced with mercapto-PEG12-acid (cas: 1032347-93-5), and the rest of the process remained unchanged, as follows: S1: Synthesis of template: (1) Add 5 parts of polyethylene oxide monomethyl ether to 30 parts of anhydrous pyridine and dissolve completely, then stir vigorously, gradually add 0.25 parts of 2-bromoisobutyryl bromide dropwise in an ice-water bath, the addition time is controlled within 25 min, then stir at 25 °C for 11 h, purify, filter, wash and dry to obtain initiator A; (2) 4.9 parts of initiator A, 0.173 parts of pentamethyldiethylenetriamine, 0.143 parts of cuprous bromide, and 5.2 parts of styrene were added to a reaction bottle, mixed, degassed, stirred at 115° C. for 2 h, purified, precipitated, and dried to obtain a bromine-terminated block copolymer; (3) Add 10 parts of bromine-terminated block copolymer to anhydrous ether and stir evenly, add 0.145 parts of allyl magnesium bromide in an ice-water bath, stir for 1.5 hours, purify, and dry to obtain an allyl-terminated copolymer; (4) adding 10.5 parts of allyl-terminated polymer to tetrahydrofuran and stirring evenly, adding 1.01 parts of mercapto-PEG12-acid and 0.25 parts of benzoin dimethyl ether, stirring under ultraviolet light for 20 hours, purifying, precipitating, and drying to obtain a template; S2: Add 11 parts of template to 30 parts of tetrahydrofuran, stir evenly, add 5.5 parts of metal precursor (mass ratio of copper chloride to nickel chloride is 1:1.65), stir at 55°C for 1.5h, add 8.5 parts of acetylacetone, stir at 60°C for 4.5h, transfer to an oven and heat treat at 70°C for 16h to obtain a mesoporous material preform; S3: The mesoporous material preform is transferred to a muffle furnace and calcined at 700° C. for 7 h in a reducing gas atmosphere to obtain a bimetallic catalyst.
[0030] Comparative Example 3: Based on Example 1, the ratio of copper salt and nickel salt was interchanged, and the other processes remained unchanged, as follows: S1: Synthesis of template: (1) Add 5 parts of polyethylene oxide monomethyl ether to 30 parts of anhydrous pyridine and dissolve completely, then stir vigorously, gradually add 0.25 parts of 2-bromoisobutyryl bromide dropwise in an ice-water bath, the addition time is controlled within 25 min, then stir at 25 °C for 11 h, purify, filter, wash and dry to obtain initiator A; (2) 4.9 parts of initiator A, 0.173 parts of pentamethyldiethylenetriamine, 0.143 parts of cuprous bromide, and 5.2 parts of styrene were added to a reaction bottle, mixed, degassed, stirred at 115° C. for 2 h, purified, precipitated, and dried to obtain a bromine-terminated block copolymer; (3) Add 10 parts of bromine-terminated block copolymer to anhydrous ether and stir evenly, add 0.145 parts of allyl magnesium bromide in an ice-water bath, stir for 1.5 hours, purify, and dry to obtain an allyl-terminated copolymer; (4) adding 10.5 parts of allyl-terminated polymer to tetrahydrofuran and stirring evenly, adding 0.31 parts of mercapto-diethylene glycol-carboxylic acid and 0.25 parts of benzoin dimethyl ether, stirring for 20 hours under ultraviolet light, purifying, precipitating, and drying to obtain a template; S2: Add 11 parts of template to 30 parts of tetrahydrofuran, stir evenly, add 5.5 parts of metal precursor (mass ratio of copper chloride to nickel chloride is 1.65:1), stir at 55°C for 1.5h, add 8.5 parts of acetylacetone, stir at 60°C for 4.5h, transfer to an oven and heat treat at 70°C for 16h to obtain a mesoporous material preform; S3: The mesoporous material preform is transferred to a muffle furnace and calcined at 700° C. for 7 h in a reducing gas atmosphere to obtain a bimetallic catalyst.
[0031] Comparative Example 4: Based on Example 1, polyethylene oxide monomethyl ether with a molecular weight of 15,000 was used, and the other processes remained unchanged, as follows: S1: Synthesis of template: (1) After 15 parts of polyethylene oxide monomethyl ether with a molecular weight of 15,000 was completely dissolved in 30 parts of anhydrous pyridine, the mixture was stirred vigorously, and 0.25 parts of 2-bromoisobutyryl bromide was gradually added dropwise in an ice-water bath. The addition time was controlled within 25 min, and then stirred at 25 °C for 11 h, purified, filtered, washed, and dried to obtain initiator A; (2) 4.9 parts of initiator A, 0.173 parts of pentamethyldiethylenetriamine, 0.143 parts of cuprous bromide, and 5.2 parts of styrene were added to a reaction bottle, mixed, degassed, stirred at 115° C. for 2 h, purified, precipitated, and dried to obtain a bromine-terminated block copolymer; (3) Add 10 parts of bromine-terminated block copolymer to anhydrous ether and stir evenly, add 0.145 parts of allyl magnesium bromide in an ice-water bath, stir for 1.5 hours, purify, and dry to obtain an allyl-terminated copolymer; (4) adding 10.5 parts of allyl-terminated polymer to tetrahydrofuran and stirring evenly, adding 0.31 parts of mercapto-diethylene glycol-carboxylic acid and 0.25 parts of benzoin dimethyl ether, stirring for 20 hours under ultraviolet light, purifying, precipitating, and drying to obtain a template; S2: Add 11 parts of template to 30 parts of tetrahydrofuran, stir evenly, add 5.5 parts of metal precursor (mass ratio of copper chloride to nickel chloride is 1:1.65), stir at 55°C for 1.5h, add 8.5 parts of acetylacetone, stir at 60°C for 4.5h, transfer to an oven and heat treat at 70°C for 16h to obtain a mesoporous material preform; S3: The mesoporous material preform is transferred to a muffle furnace and calcined at 700° C. for 7 h in a reducing gas atmosphere to obtain a bimetallic catalyst.
[0032] Performance test: (1) The bimetallic catalyst of Example 4 was subjected to performance testing, and the optimal experimental conditions were tested, and then compared with domestic and foreign competitive products. The experimental data are shown in Table 1; (2) The bimetallic catalysts prepared in the remaining embodiments and comparative examples were tested for the yield of sugar alcohols under normal pressure air conditions at 160°C, using isopropanol as the solvent and hydrogen source. The experimental data are shown in Table 2.
[0033] Table 1
[0034] Table 2
[0035] Conclusion: As shown in Table 1, the bimetallic catalyst prepared by the present invention has mild reaction conditions compared with domestic and foreign competing products, and can reach a yield of 99.5% under 160°C atmospheric pressure air conditions. The active component has a small particle size, good selectivity, high catalytic activity, and no severe toxic pollution. As shown in Table 2: In Comparative Example 1, the bromine-terminated block copolymer is not grafted with thiol-diethylene glycol-carboxylic acid, the dispersion of the template agent in the system is reduced, the ability of self-assembly is reduced, and the uniformity of the pores and pore distance of the mesoporous material is reduced, resulting in a decrease in yield; in Comparative Example 2, the thiol- When diethylene glycol-carboxylic acid is replaced by mercapto-PEG12-acid, the grafted molecular weight is too large, the possibility of entanglement and penetration between molecular chains increases, the porosity decreases, and the yield decreases; in Comparative Example 3, the ratio of copper salt and nickel salt is interchanged, the selectivity of the catalyst for hydrogenation of aldehyde to sugar alcohol decreases, the by-products increase, and the yield decreases; in Comparative Example 4, polyethylene oxide monomethyl ether with a molecular weight of 15,000 is used, the probability of entanglement and penetration between molecular chains increases, and larger, densely structured aggregates are formed, which reduces the porosity and leads to a decrease in yield.
[0036] In summary, the present invention successfully prepared a bimetallic catalyst for furfural hydrogenation by preparing a block copolymer with a specific molecular weight and containing special groups as a template, mixing it with a certain proportion of a metal precursor and a carrier precursor, drying it, and calcining it, which has good selectivity and catalytic performance.
[0037] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a bimetallic catalyst for furfural hydrogenation, characterized in that: The following steps are involved: S1: Synthesis of template: Polyethylene oxide monomethyl ether and 2-bromoisobutyryl bromide are reacted to obtain an initiator, which is then reacted with styrene to form a bromine-terminated block copolymer and grafted with poly(ethylene glycol) acid to obtain a template; S2: Add the template into tetrahydrofuran, stir evenly, add the metal precursor, stir at 50-60°C for 1-2h, add the carrier precursor, stir at 55-65°C for 4-5h, transfer to an oven and heat treat at 50-100°C for 15-18h to obtain a mesoporous material preform; S3: transferring the mesoporous material preform to a muffle furnace, and calcining it at 550-900° C. in a reducing gas atmosphere to obtain a bimetallic catalyst.
2. The method for preparing a bimetallic catalyst for furfural hydrogenation according to claim 1, wherein: The synthesis of the template comprises the following steps: (1) After polyethylene oxide monomethyl ether is completely dissolved in anhydrous pyridine, the mixture is vigorously stirred, and 2-bromoisobutyryl bromide is gradually added dropwise in an ice-water bath, with the addition time controlled at 20-30 min. The mixture is then stirred at 20-30 °C for 10-12 h, purified, filtered, washed, and dried to obtain initiator A; (2) Initiator A, pentamethyldiethylenetriamine, cuprous bromide and styrene are added to a reaction bottle, mixed, degassed, stirred at 110-120° C. for 1-3 h, purified, precipitated and dried to obtain a bromine-terminated block copolymer; (3) adding anhydrous ether to the bromine-terminated block copolymer and stirring evenly, adding allyl magnesium bromide in an ice-water bath, stirring for 1 to 2 hours, purifying, and drying to obtain an allyl-terminated copolymer; (4) Add the allyl-terminated copolymer into tetrahydrofuran and stir evenly, add mercapto-polyethylene glycol-carboxylic acid and benzoin dimethyl ether, stir under ultraviolet light for 20 to 22 hours, purify, precipitate, and dry to obtain a template.
3. The method for preparing a bimetallic catalyst for furfural hydrogenation according to claim 1, wherein: The molecular weight of the polyethylene oxide monomethyl ether is 5000-8000; the metal precursor comprises a copper salt and a nickel salt in a molar ratio of 1.5-1.6:1; the copper salt comprises one of copper chloride, copper nitrate, and copper acetylacetonate; the nickel salt comprises one of nickel chloride, nickel nitrate, and nickel acetylacetonate; the carrier precursor comprises one of acetylacetone, citric acid, and polyvinyl pyrrolidone.
4. The method for preparing a bimetallic catalyst for furfural hydrogenation according to claim 2, wherein: The mercapto-polyethylene glycol-carboxylic acid includes one of mercapto-diethylene glycol-carboxylic acid, mercapto-triethylene glycol-carboxylic acid and mercapto-tetraethylene glycol-carboxylic acid.
5. The method for preparing a bimetallic catalyst for furfural hydrogenation according to claim 1, characterized in that: The mesoporous material preform comprises the following raw materials, calculated by weight: 10-12 parts of a template, 30-35 parts of tetrahydrofuran, 5-6 parts of a metal precursor, and 8-9 parts of a carrier precursor.
6. The method for preparing a bimetallic catalyst for furfural hydrogenation according to claim 2, characterized in that: The template comprises an allyl-terminated copolymer, mercapto-diethylene glycol-carboxylic acid and benzoin dimethyl ether in a molar ratio of 1:1.5-1.7:0.9-1.
1.
7. The method for preparing a bimetallic catalyst for furfural hydrogenation according to claim 2, characterized in that: The initiator A comprises the following raw materials, calculated in parts by mass: 4.8-5.2 parts of polyethylene oxide monomethyl ether and 0.24-0.26 parts of 2-bromoisobutyryl bromide; the bromine-terminated block copolymer comprises the following raw materials, calculated in parts by mass: 4.8-5.0 parts of initiator A, 0.17-0.18 parts of pentamethyldiethylenetriamine, 0.14-0.15 parts of cuprous bromide and 5.1-5.3 parts of styrene; the allyl-terminated copolymer comprises the following raw materials, calculated in parts by mass: 9.5-10.5 parts of bromine-terminated block copolymer and 0.14-0.15 parts of allylmagnesium bromide.
8. The method for preparing a bimetallic catalyst for furfural hydrogenation according to claim 1, characterized in that: During the heat treatment process, the temperature is 50-100°C, preferably 60-80°C, and the time is 15-18 hours; during the calcination process, the temperature is 550-900°C, preferably 650-800°C, and the time is 6-8 hours.
9. A bimetallic catalyst prepared according to the preparation method of a bimetallic catalyst for furfural hydrogenation according to any one of claims 1 to 8.